2016
DOI: 10.1016/j.ijmyco.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Increased detection of smear-negative pulmonary tuberculosis by GeneXpert MTB/RIF® assay after bleach concentration

Abstract: Testing of a single sputum sample by Xpert can reach reasonable sensitivity and results would be available on the same day, avoiding loss of patients and treatment delay. The sensitivity of Xpert was improved after bleach concentration and pelleting, although its added value needs further study on a larger scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 18 publications
6
20
1
Order By: Relevance
“…However, the high proportion (49.3%) of smear-negative Xpert-positive results could be partially ascribed to performing smear microscopy directly on unprocessed sample, differently from Xpert that was carried out on concentrated sample. In line with this evidence, recently, Tadesse and colleagues demonstrated that bleach concentration and pelleting of smear-negative samples increase Xpert sensitivity from 63.2% to 73.8% [34]. …”
Section: Discussionmentioning
confidence: 75%
“…However, the high proportion (49.3%) of smear-negative Xpert-positive results could be partially ascribed to performing smear microscopy directly on unprocessed sample, differently from Xpert that was carried out on concentrated sample. In line with this evidence, recently, Tadesse and colleagues demonstrated that bleach concentration and pelleting of smear-negative samples increase Xpert sensitivity from 63.2% to 73.8% [34]. …”
Section: Discussionmentioning
confidence: 75%
“…In the Patient Selection domain, we considered 55 studies (64%) to have low risk of bias because the study enrolled a consecutive or random sample of eligible participants and avoided inappropriate exclusions. We considered 16 studies (19%) to have high risk of bias because the study did not avoid inappropriate exclusions: 13 studies enrolled participants whose sputum specimens were primarily or exclusively smear‐positive or smear‐negative ( Barnard 2015 ; Friedrich 2011 ; Jo 2016 ; Lee 2013 ; Le Palud 2014 ; Meyer 2017 ; Mok 2016 ; Moure 2011 ; Tadesse 2016 ; Theron 2013 ; Van Rie 2013 ; Walusimbi 2013a ; Williamson 2012 ) and three studies exclusively enrolled participants who had previously received tuberculosis treatment ( Meawed 2016 ; Metcalfe 2015 ; Pimkina 2015 ). In addition, we considered 15 studies (17%) to have unclear risk of bias because the manner of participant selection was not stated ( Atwebembeire 2016 ; Barmankulova 2015 ; Bates 2013a ; Boum 2016 ; Chen 2017 ; Huang 2015 ; Kim CH 2015 ; Luetkemeyer 2016 ; Mbelele 2017 ; Moussa 2016 ; Mutingwende 2015 ; Nosova 2013a ; Reechaipichitkul 2017 ; Shao 2017 ; Shenai 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the Patient Selection domain, we considered 36 studies (63%) to have low risk of bias because the study enrolled a consecutive or random sample of eligible participants and avoided inappropriate exclusions. We considered 10 studies (18% ) to have high risk of bias because the study did not avoid inappropriate exclusions and instead enrolled participants preselected on the basis of their sputum specimens being either smear‐positive or smear‐negative or the study exclusively enrolled retreatment participants ( Ali 2017 ; Friedrich 2011 ; Lee 2013 ; Le Palud 2014 ; Makamure 2017 ; N'Guessan 2016 ; Tadesse 2016 ; Theron 2013 ; Van Rie 2013 ; Williamson 2012 ). We considered 11 studies (19%) to have unclear risk of bias because the manner of participant selection was not reported ( Barmankulova 2015 ; Barnard 2015 ; Bates 2013a ; Huang 2015 ; Kim CH 2015 ; Luetkemeyer 2016 ; Meawed 2016 ; Moussa 2016 ; Nosova 2013a ; Pimkina 2015 ; Singh 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethiopia remains a high burden country for tuberculosis and most cases are smear negative (58.9%) (11). Gene Xpert has increased the diagnostic yield in smear negative patients (12), however, a signi cant number of patients still undergo tuberculosis treatment based on clinical observation alone. In our patient population, 7 of 18 patients suspect of TB but who were originally smear negative had tuberculosis con rmed with BAL.…”
Section: Discussionmentioning
confidence: 99%